2022
DOI: 10.1155/2022/7934690
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Study of Endometriosis and Normal Endometrium Based on Ultrasound Observation

Abstract: In order to compare the microscopic ultrastructure of eutopic endometrium and normal endometrium in patients with endometriosis, to study the specific pathogenesis of endometriosis. In this paper, on the basis of using B-ultrasound technology, several patients with endometriosis were subjected to B-ultrasound to observe the ultrastructure of the eutopic uterine endometrium and compared with the pictures of normal endometrium to carry out the specific analysis between the two ultrastructural comparisons. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%